Finding Science with Science: Evaluating a Domain and Scientific Ontology User Interface for the Discovery of Scientific Resources. Issue 4 (26th December 2012) - Stock, Kristin; Karasova, Vera; Robertson, Anne; Roger, Guillaume; Small, Mark; Bishr, Mohamed; Ortmann, Jens; Stojanovic, Tim; Reitsma, Femke; Korczynski, Lukasz; Brodaric, Boyan; Gardner, Zoe
Abstract: Current approaches to the discovery of scientific resources (publications, data sets and web services) are dominated by keyword search. These approaches do not allow scientists to search on the deeper semantics of scientific resources, or to discover resources on the basis of the scientific approaches taken. This article evaluates a user interface that allows users to discover scientific resources through structured knowledge in the form of ontologies describing the domain and the scientific knowledge inherent within the scientific resource, and also through informal user tags. These combined capabilities provide scientists with new and powerful options for resource discovery. A qualitative user evaluation explored how scientists felt about the approach for resource discovery in the context of their scientific work. The study showed that marine scientists were enthusiastic about the capabilities of such an approach and appreciated the ability to browse the visual structure of the knowledge and query on scientific method but, overall, preferred the use of tags over ontologies. The exploratory nature of the user study was used to identify future directions for such improvements.